Steam Explosion Pretreatment Changes Ruminal Fermentation in vitro of Corn Stover by Shifting Archaeal and Bacterial Community Structure - Wang, Kun; Nan, Xuemei; Tong, Jinjin; Zhao, Guangyong; Jiang, Linshu; Xiong, Benhai (Frontiers in Microbiology, 2020)
Steam explosion is an environment-friendly pretreatment method to improve the subsequent hydrolysis process of lignocellulosic biomass. Steam explosion pretreatment improved ruminal fermentation and changed fermentation pattern of corn stover during ruminal fermentation in vitro. The study gave a comprehensive insight into how stream explosion pretreatment shifted archaeal and bacterial community structure to change ruminal fermentation in vitro of corn stover. Results showed that steam explosion pretreatment dramatically improved the apparent disappearance of dry matter (DM), neutral detergent fiber (NDF), and acid detergent fiber (ADF). Steam explosion pretreatment significantly increased the molar proportion of propionate and decreased the ratio of acetate to propionate. At archaeal level, steam explosion pretreatment significantly increased the relative abundance of Methanobrevibacter, which can effectively remove metabolic hydrogen to keep the fermentation continuing. At bacterial level, the shift in fermentation was achieved by increasing the relative abundance of cellulolytic bacteria and propionate-related bacteria, including Spirochaetes, Elusimicrobia, Fibrobacteres, Prevotella, Treponema, Ruminococcus, and Fibrobacter.